A profile of sexually active male adolescent high school students in Lima, Peru - Jesús L. Chirinos; Victor C. Salazar; Claire D. Brindis
To document knowledge and attitudes regarding sexuality and sexual practices of male adolescent high school students in Lima, Peru, a self-administered, anonymous survey was completed by 991 male adolescents aged 12-19 as part of a School-Based Sex Education Intervention model. Questions concerned sociodemographic information; family characteristics; personal activities; knowledge and attitudes regarding sexuality; sexual experience; and contraceptive use. Knowledge related to sexuality was limited. Males tended to mainly discuss sexuality with their male peers (49.8%). Attitudes towards sexual activity and condom use were largely positive, although some males expressed ambivalent feelings towards the latter. Of the sample, 43% had ever had sex; age at first sexual intercourse was 13 years. While 88% of the sample would use condoms, 74% also gave reasons for not using them. Sexual activity was related to age, ever having repeated a grade, living with only one parent or in a mixed family, activities such as going to parties, use of alcohol, tobacco, and drugs, and viewing pornographic videos or magazines. Many male adolescents were at risk of causing an unintended pregnancy or acquiring an STD.